Uncovering the effects of grazing exclusion duration on plant richness and biomass in alpine grasslands using the price equation - Pu, Xin; Feng, Tan; Sun, Lei (Frontiers in Plant Science, 2026)
Grazing exclusion is a key strategy for restoring degraded alpine grasslands. However, the mechanisms underlying plant species richness and biomass responses to long-term enclosure, particularly species turnover and biomass redistribution, remain unclear. This study compared plant community composition, diversity, and biomass across alpine grasslands on the Qinghai–Tibet Plateau enclosure for 2, 6, 13, and 18 years and free-grazing sites. The Price equation was used to quantitatively partition the independent contributions of lost, gained, and persisting species to changes in diversity and biomass, revealing how the long-term grazing exclusion affects biodiversity and biomass. After 2 years of enclosure, both diversity and biomass increased simultaneously. The biomass increase was primarily derived from the increased biomass of persisting species, while newly gained species contributed little. After 6 years, biomass reached peak value due to further increases in the biomass of persisting gramineous species. However, the loss of weedy species and reduction in species gains caused a diversity decline. After 13 and 18 years of enclosure, the biomass of persisting species began to decline, leading to a gradual decrease in total biomass. In summary, short-term enclosure should prioritize the recovery and conservation of native species rather than the colonization by new species. During the mid-term, attention should be paid to the potential negative impact of overgrown native gramineous species on overall diversity. Long-term grazing exclusion should be avoided where possible to prevent ecosystem degradation. This study provides a novel paradigm for alpine grassland restoration by disentangling community-level dynamic processes.